Spatial Accounting of Environmental Pressure and Resource Consumption Using Night-light Satellite Imagery - Mellino, Salvatore; Ripa, Maddalena; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Modern societies and economies are highly dependent on fossil energy for their survival. Unfortunately fossil energy resources and minerals are non-renewable and represent finite stocks. Consequently, societies and economies (production, trade and consumption modes) should be reorganized according to the awareness of less resource availability in the future. “ Degrowth” and “prosperous way down patterns” have been suggested in order to avoid economic collapse and global societal turmoil and conflicts. This work assesses the dependence of a regional economy (Campania Region, Southern Italy) on non-renewable resources, by means of joint use of spatial modeling and Emergy Accounting. The Emergy method takes into account all the free environmental inputs (such as sunlight, wind, rain, geothermal heat) as well as the input flows of mineral and fossil energy resources, expressed in terms of their solar energy equivalents. Nonrenewable resources used within the regional economy were correlated to nighttime satellite images via GIS (Geographic Information System) methodology, to explore the load of human activities on land- scape and ecological communities and to define a human disturbance gradient throughout the Region. This gradient was expressed by means of an emergy-based indicator, the Landscape Development Intensity index (LDI). Results show a high dependence of Campania Region economy from imported resources (about 85% of the total emergy used, U) and a high concentration of non-renewable flows in Napoli and Caserta Provinces. These two regional areas have much higher LDI indices, 44 and 36 respectively, suggesting the need for appropriate land use management actions capable to lower the environmental pressure to more sustainable levels.